Defects in the Immune System of Mice Infected with Lymphocytic Choriomeningitis Virus - Bro-Jørgensen, K. (1974)
Acute lymphocytic choriomeningitis virus infection of adult mice is associated with general immunosuppression, which develops during the 2nd week of the infection and persists for a period of 2 to 3 months. Studies of some cellular events in the immune system of infected mice brought to light a number of findings which seemed relevant to this immunosuppressive effect. Colony-forming stem cells, which may act as the precursors of the lymphoid cells, were temporarily inhibited during the first period of the infection. Presumably this inhibition also affected the thymus cells, which decreased dramatically at the same time. At a later stage of infection, defects developed within the population of immunocompetent cells, and this was most probably a consequence of the preceding suppression of the precursor cells. The defects in the immunocompetent cells were temporally related to the immunosuppression and seemed to be the ultimate cause of this phenomenon. At all events, antibody-forming cells were not damaged by the virus. In studies of neonatally infected baby mice, it was found that the development of immunological responsiveness was completely abolished for the first 2 weeks of life. It is therefore probable that the generation of immunocompetent cells was also affected in the babies. Evidence was obtained supporting the hypothesis that this effect played an important role for the induction of tolerance to the virus in the neonatally infected mice.